2020
DOI: 10.1111/1755-6724.14338
|View full text |Cite
|
Sign up to set email alerts
|

Genesis for Rare Earth Elements Enrichment in the Permian Manganese Deposits in Zunyi, Guizhou Province, SW China

Abstract: The Zunyi manganese deposits, which formed during the Middle to Late Permian period and are located in northern Guizhou and adjacent areas, are the core area of a series of large‐medium scale manganese enrichment minerogenesis in the southern margin and interior of the Yangtze platform, Southern China. This study reports the universal enrichment of rare earth elements (REEs) in Zunyi manganese deposits and examines the enrichment characteristics, metallogenic environment and genesis of REEs. The manganese ore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…In addition, the silicified rocks differ from place to place in regard to the clast types, sizes, shapes and depositional successions. Xu et al (2020) recently measured the silicon isotopes and REE values of these massive silicified rocks and suggested that the observed brecciation and silicification resulted from hydrothermal migration along potential syndepositional faults during the stage of the ELIP.…”
Section: Facies Interpretations and Changes In Central Guizhoumentioning
confidence: 99%
“…In addition, the silicified rocks differ from place to place in regard to the clast types, sizes, shapes and depositional successions. Xu et al (2020) recently measured the silicon isotopes and REE values of these massive silicified rocks and suggested that the observed brecciation and silicification resulted from hydrothermal migration along potential syndepositional faults during the stage of the ELIP.…”
Section: Facies Interpretations and Changes In Central Guizhoumentioning
confidence: 99%
“…The dynamic matching relationship between source and caprock in well GS-1 is not ideal for reservoir formation. Due to the Lower Cambrian source rock being close to the middle belt of the Emeishan basalt eruption area (Xu et al, 2020), under high heat flow and temperature, it rapidly matured and generated hydrocarbons. The kerogen matured sharply and the vitrinite reflectance reached more than 3.5% by the end of the Early Permian, the hydrocarbon generating potential being exhausted.…”
Section: Shale Is the Caprock In An Ultra-deep Exploration Areamentioning
confidence: 99%
“…Although the sampling wells already exist in their own sedimentary environments of different salinities, some trace elements of the samples used for the thermal simulation experiments have also been tested, aiming to ensure that the three samples unquestionably represent different salinities. As the element B and the ratios of B to Ga and Sr to Ba can effectively represent the paleosalinity, they are used to identify the salinity values of W18-5, H7-18 and CH9, the value of the paleosalinity specifically having a positive correlation with B, B/Ga and Sr/Ba (You et al, 2003;Xu et al, 2020). As shown in Table 4, all three indicators show that W18-5 has the highest salinity, followed by H7-18 and CH9.…”
Section: Representativeness Of Samplesmentioning
confidence: 99%